Validitas dan Reliabilitas Tes Melengkapi Wacana pada Penelitian Pragmatik Bahasa Antara (Interlanguage Pragmatics) - Bayu Aryanto; Syamsul Hadi; Tatang Hariri (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
This article is intended to provide insight to researchers who are still doubtful about the validity and reliability of one of the data collection methodologies, namely the method of discourse completion test in general pragmatic research and interlanguage pragmatics. The literature review was used in the preparation of this article to get the comprehensive picture of the completion discourse test. One of the results is that data collection methods using completion discourse test have advantages and disadvantages. One drawback is that the authenticity of the data and the limitations on the data quality obtained from an informant or respondent, even in certain studies, is judged to not be able to capture sufficiently good data. However, this method is a very good method to find stereotype data because researchers can obtain abundant data in sufficient quantities by this method. In addition, this completion discourse test is very effective in the language study in the cross-cultural domain. This method can be used to capture data in two or more languages with different cultural backgrounds as Blum-Kulka and Olshtain did (in 1984). The control of research variables by using the completion discourse test is considered better because one of the research variables in pragmatic studies is the context of conversation which is very dynamic so that there needs to be controlled. Controlling this research variable is expected to be able to make conclusions that are more conical answer for the research problem.Keywords: discourse completion test, interlanguage pragmatics, research variable control